2006
DOI: 10.1128/aac.00362-05
|View full text |Cite
|
Sign up to set email alerts
|

Novel Conjugate of Moxifloxacin and Carboxymethylated Glucan with Enhanced Activity againstMycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis is an intracellular pathogen that persists within macrophages of the human host. One approach to improving the treatment of tuberculosis (TB) is the targeted delivery of antibiotics to macrophages using ligands to macrophage receptors. The moxifloxacin-conjugated dansylated carboxymethylglucan (M-DCMG) conjugate was prepared by chemically linking dansylcadaverine (D) and moxifloxacin (M) to carboxymethylglucan (CMG), a known ligand of macrophage scavenger receptors. The targeted deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Achieving an effective concentration of drug by oral administration and a complete cure is complicated by the difficulty of delivering drugs to the sites deep within the lungs where Mycobacterium tuberculosis resides. Several studies have attempted to improve the delivery of drugs into the lungs [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Such targeted delivery of drugs is expected to improve the treatment of TB, decrease the necessary doses, and reduce systemic sideeffects.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving an effective concentration of drug by oral administration and a complete cure is complicated by the difficulty of delivering drugs to the sites deep within the lungs where Mycobacterium tuberculosis resides. Several studies have attempted to improve the delivery of drugs into the lungs [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Such targeted delivery of drugs is expected to improve the treatment of TB, decrease the necessary doses, and reduce systemic sideeffects.…”
Section: Introductionmentioning
confidence: 99%
“…tuberculosis within macrophages [36]. But this conjugation is not supportive for conjugation with PA-824 since Carboxymethylglucan has been shown to have antioxidant activities [37] which could counteract the essential ROS generation by PA-824 for bactericidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Schwartz and coworkers explored the use of moxifloxacin-conjugated dansylated carboxymethylglucan (45). It was found that the conjugated glucan was concentrated in the macrophages of lungs and spleen.…”
Section: Treatment Of Tb and Other Mycobacterial Diseasementioning
confidence: 98%